ANALYSIS OF CONSUMER BEHAVIOUR IN PURCHASE DECISION-MAKING VIA E-COMMERCE PLATFORMS: A QUALITATIVE STUDY OF GENERATION Z - Hasrul Hasrul; Muhamad Apep Mustofa (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze consumer behavior in purchasing decisions for products via e-commerce platforms using a qualitative approach amongst Generation Z. The research was conducted in January–February 2026, involving informants aged 18–26 who actively use the Shopee, Tokopedia, and TikTok Shop platforms. Data collection was carried out through in-depth interviews, observation and documentation, whilst data analysis utilized NVivo 14 software through the stages of open coding, axial coding and selective coding. The results of the study revealed four main themes that shape the purchasing decision-making process, namely Digital Impulse & Discovery, Information Triangulation, Value-for-Money & Risk Evaluation, and Seamless Checkout & Post-Purchase Validation. The findings indicate that Generation Z’s purchasing decisions do not follow a linear path but are influenced by exposure to social media, user-generated content, product value assessment, seller credibility, and the ease of digital payments. Social media acts as a trigger for the emergence of needs, whilst video reviews serve as the most trusted source of information before making a purchase. Furthermore, promotions, free delivery, and flexible payment methods accelerate the decision-making process. This study contributes to the development of digital marketing management research by enriching our understanding of Generation Z consumer behavior within the e-commerce ecosystem, whilst also serving as a reference for businesses in formulating more effective digital marketing strategies that are oriented towards consumer needs.